ANALISIS PENENTUAN LOKASI ATM MENGGUNAKAN DIAGRAM VORONOI PADA BANK SYARIAH - Kosala Dwidja Purnomo; Fitria Iga Pramesti (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2022)
Determining the right location for distribution of ATM Bank Syariah in Jember Regency considers several parameters including public facilities, ease of access and population. The problem in determining of location is called Facility Location Problem (FLP). The problem solving of location determination can use Voronoi diagram, which is to divide each desired region into several parts. Each part of the region represents a single point of location. Each point of location will be mapped with each point of the nearest location. Determining the nearest location point using Euclid distance. Determination of location based on parameters by giving a score on each data and giving a weight value on each parameter. From the score value and weight values owned will be obtained the total weight value of each region. The region with the highest weight value is designated as the district center. Each subdistrict center will have several service areas based on the nearest Google Maps distance. Determinating location of ATM Bank Syariah will be carried out based on parameters potential analysis in each service area.